ANALYSIS OF THE EFFECT OF HOLE GEOMETRY ON THE CATALYST ON EXHAUST GAS EMISSIONS IN MOTORCYCLE EXHAUST - Bintara Adi Putra; Oleh .; Farradina Choria Suci (Universitas Muhammadiyah Semarang, 2022)
The increasing number of motorized vehicles has a direct impact on air pollution caused by vehicle exhaust gases. A catalytic converter is a tool used to reduce exhaust emissions by reducing exhaust emissions. The catalyst is the main component in the catalytic converter which functions as a reducing agent. In this study, the material used as a catalyst is brass. This study aims to determine the effect of the geometry of the catalyst on the distribution of pressure, temperature, and velocity and to determine the exhaust gas emissions that come out of the combustion chamber into the environment after adding a catalyst, as well as to compare the results of testing exhaust emissions on a standard exhaust with an exhaust that has added a catalyst. The method used in this study is the simulation method using Solidwork 2019 software and experimental testing using agass analyzer. From experimental testing, the most optimal catalyst geometry will be sought to reduce exhaust gas emission levels such as CO, HC, and CO2 levels. The result of the largest pressure distribution occurs in the geometry of list IV and the smallest average pressure occurs in the standard exhaust The largest temperature distribution occurs in the geometry of the catalyst III standard exhaust. The largest average velocity distribution occurs in the standard exhaust and the smallest on the catalyst geometry IV. The results of the experimental test the most optimal percentage reduction in exhaust emissions occurred in the geometry of the alist IV which was compared with the results of the standard exhaust test with results of CO 15.153%, HC 19.713%, and CO2 9.275%.